Topological Metal MoP Nanowire for Interconnect - Han, Hyeuk Jin; Kumar, Sushant; Jin, Gangtae; Ji, Xiaoyang; Hart, James L.; Hynek, David J.; Sam, Quynh P.; Hasse, Vicky; Felser, Claudia; Cahill, David G.; Sundararaman, Ravishankar; Cha, Judy J. (Advanced Materials, 2023)
The increasing resistance of copper (Cu) interconnects for decreasing dimensions is a major challenge in continued downscaling of integrated circuits beyond the 7 nm technology node as it leads to unacceptable signal delays and power consumption in computing. The resistivity of Cu increases due to electron scattering at surfaces and grain boundaries at the nanoscale. Topological semimetals, owing to their topologically protected surface states and suppressed electron backscattering, are promising candidates to potentially replace current Cu interconnects. Here, we report the unprecedented resistivity scaling of topological metal molybdenum phosphide (MoP) nanowires, and it is shown that the resistivity values are superior to those of nanoscale Cu interconnects <500 nm2 cross-section areas. The cohesive energy of MoP suggests better stability against electromigration, enabling a barrier-free design. MoP nanowires are more resistant to surface oxidation than the 20 nm thick Cu. The thermal conductivity of MoP is comparable to those of Ru and Co. Most importantly, it is demonstrated that the dimensional scaling of MoP, in terms of line resistance versus total cross-sectional area, is competitive to those of effective Cu with barrier/liner and barrier-less Ru, suggesting MoP is an attractive alternative for the scaling challenge of Cu interconnects.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electron scattering; energy-efficient computing; interconnects; topological metals